You aren't here: Reimagining the place of graffiti production in heritage studies. (February 2015) - Edwards-Vandenhoek, Samantha
Centred on the theorization, design and implications of the Sydney Graffiti Archive, this article considers how the virtual image archive intervenes in the experience of graffiti to shift negative perceptions about graffiti as damage to cultural heritage. As a parallel discursive arena (see Fraser, 1995; Hauser, 1998), the Sydney Graffiti Archive infiltrates and transgresses normative conceptions of place and cultural narratives through the formation and circulation of unofficial visual discourses embedded in graffiti photographs. This article evaluates the place of the archive as a heuristic device and heterotopic entity and encourages new ways of seeing illicit graffiti, and other everyday digital cultures of commemoration, in that it reshapes present relations to the past through photographic reframing, image digitization, interface design and user engagement. Essentially, this research is about hacking into, recovering and honouring graffiti's discursive sites to reimagine graffiti's place as digital heritage.